Immaturity vs paedomorphism: a rhinesuchid stereospondyl postcranium from the Upper Permian of South Africa - Pawley, Kat; Warren, Anne (Bernard Price Institute for Palaeontological Research, 2004)
The postcranial skeleton of a medium-sized rhinesuchid from the Late Permian Dicynodon Assemblage Zone of South Africa is described. The well-preserved, articulated specimen consists of a partial skull, vertebral column and ribs, pectoral girdle, proximal limb elements, and ventral scales. Interesting features rarely preserved in stereospondyls include the extensive ventral scales and the pectinate anterior border of the interclavicle. SAM-PK-K10021 is of an average size for a rhinesuchid, but possesses a poorly ossified postcranial skeleton in comparison to larger rhinesuchid specimens. The scapulocoracoid lacks an ossified coracoid plate, the humerus lacks a supinator process, and the femur lacks a well-developed internal trochanter and adductor blade. Despite its relatively large size, SAM-PK-K10021 is an immature stage of a large rhinesuchid, thus contributing to our knowledge of the changes to the postcranial skeleton that occur during ontogeny. The assessment of heterochronic processes, especially paedomorphism, in the postcranial skeleton of temnospondyls, and the implications for cladistic analysis, are discussed.
Keywords: Rhinesuchidae, postcranial skeleton, stereospondyl, temnospondyl, ontogeny, heterochrony.